Costly intermediation and the big push - Zsolt Becsi; Ping Wang; Mark A. Wynne (Federal Reserve Bank of Atlanta, 1998)
Many existing theories of financial intermediation have difficulty explaining why financial activity can generate large real effects. This paper argues that the large real effects may reflect a multiplicity of equilibria. The multiple equilibria in this paper are generated by the dynamic interactions between the savings decisions of workers and the monopolistically competitive behavior of banks. We characterize the equilibria by showing the comparative-static responses of key aggregates to changes in the pure rate of time preference, investment uncertainty, and bank costs. We find that the results depend crucially on the intertemporal elasticity of labor supply and the aggregate level of employment. Small changes in the financial system may cause the economy to shift between low- and high-employment equilibria. The high-employment, high real interest rate equilibrium is consistent with the development experience of Japan, Korea, and Taiwan with repressed financial systems.
Keywords: 330; Economic development